2014
DOI: 10.1101/cshperspect.a008524
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation and Adaptation in Africa: Implications for Human Evolution and Disease

Abstract: Because modern humans originated in Africa and have adapted to diverse environments, African populations have high levels of genetic and phenotypic diversity. Thus, genomic studies of diverse African ethnic groups are essential for understanding human evolutionary history and how this leads to differential disease risk in all humans. Comparative studies of genetic diversity within and between African ethnic groups creates an opportunity to reconstruct some of the earliest events in human population history and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 194 publications
(248 reference statements)
3
76
0
Order By: Relevance
“…For example, in East Africa, other instances of the lactase persistence variant have arisen in the LCT genomic region, and, in high latitudes of Asia, other variants in different genes that lighten skin pigmentation have spread to high frequency (see review in Gomez et al 2014). Therefore, it seems that when distant human populations are faced with similar selection pressures, independent evolutionary responses can take place.…”
Section: Darwinian Selection Within Europementioning
confidence: 99%
“…For example, in East Africa, other instances of the lactase persistence variant have arisen in the LCT genomic region, and, in high latitudes of Asia, other variants in different genes that lighten skin pigmentation have spread to high frequency (see review in Gomez et al 2014). Therefore, it seems that when distant human populations are faced with similar selection pressures, independent evolutionary responses can take place.…”
Section: Darwinian Selection Within Europementioning
confidence: 99%
“…284 Finally, genetic variation is substantially greater among black 285 women from sub-Saharan Africa than white Europeans [36]; it is 286 thus conceivable that each African ethnic group within these 287 countries has its own STV threshold, and that our study lacks the 288 power to show this.…”
mentioning
confidence: 97%
“…STV 30 is the best predictive criterion for fetal well-being [5,7], and the 31 relation between reduced STV and the degree of neonatal acidosis 32 has been demonstrated [5,7-9] Some authors have suggested that maternal race influences the 34 FHR parameters considered in standard visual FHR monitoring. 35 Accordingly, compared to the fetuses of white women, fetuses of 36 black women are significantly less reactive [10], have a higher 37 basal heart rate [11], and are more likely to have micro-fluctuating 38 or flat FHR during labor and delivery [12]. 39 To our knowledge, only one study has used computerized FHR 40 analysis to examine the influence of maternal geographic origin on 41 FHR variation.…”
mentioning
confidence: 99%
“…In this collection, scholars of genetic variation and evolution in the major geographic regions of the world have outlined both known and more recent genetic studies (Gomez et al 2014;Majumder and Basu 2014;Ruiz Linares 2014;Veeramah and Novembre 2014). Their research, and the complementary works of others, allows us to make three major novel inferences.…”
Section: A Brief Synthesis Of Recent Human Evolutionmentioning
confidence: 99%